Penguatan dan Pendampingan Pelaku Usaha Mikro Kecil dan Menengah (UMKM) di Desa Cikujang, Serangpanjang, Subang, Jawa Barat - Serly Wulandari (Civitas Consecratio: Journal of Community Service and Empowerment, 2022)
The maindset of Micro, Small and Medium Enterprises (MSME) players who think that without the need for various marketing strategies, products will still sell well in the market, this is one of the factors causing the sale of products with simple and plain packaging. In fact, the packaging design of a marketed product is the first thing that is seen and can affect the psychology of a consumer, it is also one of the special requirements in making a Business License through Online Single Submission (OSS), both the Business Identification Number (NIB) and the Certificate of Fulfillment of Commitments Home Industry Processed Food Production (SPP-IRT). This service activity aims to provide reinforcement in the form of increasing literacy related to product packaging designs and business license as well as assistance in making new packaging designs with complete labels and Business License in the form of NIB and SPP-IRT through OSS to Productive MSME actors in Cikujang Village. This service activity method is carried out through FGD with Productive MSME in Cikujang Village, education through socialization and training related to product packaging design and business license as well as simulation and assistance to make product packaging designs with complete labels and business license. The findings in this service activity, namely the existence of various entrenched negative maindsets, limited ability and knowledge related to market developments, product packaging design and business license and technology, limited facilities and infrastructure related to technology in making product packaging designs and registering business license through OSS for Productive MSME actors in Cikujang Village. This community service activity can be concluded to have a positive impact with the output of the activity in the form of new product packaging designs with complete labels for MSME for chips and village snacks and the issuance of business license in the form of 3 (three) NIB and 2 (two) SPP-IRT.